Endocrine therapy in epithelial ovarian cancer. Issue 2 (1st February 2017) - Langdon, Simon P; Gourley, Charlie; Gabra, Hani; Stanley, Barbara
ABSTRACT: Introduction: The estrogen receptor (ER) is expressed at high levels in many epithelial ovarian cancers (EOC) and represents a potential target for endocrine therapy. Both anti-estrogens and aromatase inhibitors have been evaluated in phase II clinical trials. Areas covered: We present an overview of the phase II and phase III trials of anti-estrogens (tamoxifen and fulvestrant) and aromatase inhibitors (letrozole, anastrazole and exemestane) undertaken in epithelial ovarian cancer identified through a Pubmed search. We describe predictive biomarkers that are being investigated to identify responsive cancers. Expert commentary: The efficacy of endocrine therapy in epithelial ovarian cancer is likely to be confined to histological subtypes with the highest ER expression while low grade serous ovarian cancer appears to be one subgroup with good sensitivity to these agents. The low toxicity profile of these agents is favourable although their use is unlicensed and the optimal setting undefined. Prospective clinical trials of endocrine agents in the early relapse and maintenance settings are urgently required to establish their definitive role in the management of epithelial ovarian cancer.